Understanding athlete brand life cycle. Issue 2 (1st February 2021) - Hasaan, Ali; Biscaia, Rui; Ross, Stephen
Abstract: The purpose of this study was to present a framework to aid understanding athlete brand life cycle and how to extend it. A thorough review of the literature was conducted to create the proposed framework. Five stages were identified including brand introduction, brand growth, brand maturity, brand decline and brand reinvention, as well as athlete capital that may occur for some athletes. This study extends prior research by providing an initial idea on how to develop and manage an athlete brand life cycle throughout his/her career.